L’art et la manière. Artistes des arts numériques, positionnement professionnel et créativité artistique en France et en Allemagne - Geneviève Vidal; Anne Gagnebien; Eva-Maria Schultze; Christian Papilloud (Communiquer)
This article introduces to an empirical investigation carried out over 20 months about 25 interviewees (April 2015 – November 2016) regarding the professional positioning of artists working in the field of digital arts in France and Germany. It is the product of an interdisciplinary collaboration between sociologists and researchers in the field of communication sciences. It extends a case study undertook in France over 12 months (January 2013 – January 2014) about 12 artists or actors of NetArt, which has underlined a cycle of professional positioning whose four main steps are 1) the mobilization of a large and various public around artistic projects, 2) the public participation to the artists’ work, 3) the diversion of digital technologies, and 4) the promotion of artists’ work in the economic sectors of digital innovations. Our inquiry in France and Germany confirms the most important steps of this cycle. However, it takes a different meaning for our French and German interviewees. According to our French interviewees, it is bound to the relation between digital arts and contemporary art. According to our German interviewees, it has to be developed away from such strong reference to art.